Edukasi Meningkatkan Kesadaran Imunisasi Di Wilayah Pesisir - Mega Octamelia; Ririn Arianti (Pusat Riset dan Inovasi Nasional, 2022)
Data on immunization coverage in Indonesia from the Indonesian Ministry of Health shows a decline since the COVID 2020 pandemic. Compared to 2019, this decrease in immunization coverage occurred at the provincial to district level. Some of the causes of this low coverage of complete basic immunization are the rules of activity restrictions during the COVID 19 pandemic, the lack of knowledge and awareness of parents to immunize their babies, and there is still a sense of anxiety related to the side effects of immunization. The purpose of the activities carried out is to provide education by persuasion so that families can understand the importance of complete immunization for children's health. The targets in the implementation of this community service are cadres and mothers who have babies in Neighborhood Association 10 and Neighborhood Association 11 in the Coastal Area of Pantai Amal Village. The stages of service are divided into 3, namely; preparation stage, implementation stage (pretest, material delivery, discussion and posttest), and final stage. The results of providing education show that the education provided has increased participants' understanding and awareness of immunizing their babies. Suggestions after this service activity are the need for a persuasive approach and the need to develop more appropriate communication media given to mothers according to their needs.